Song Translation of Speechless by Naomi Scott: Metaphor and Untranslatability - Siti Lutfiah Rabiyatul Adawiyah; Annisa Nurul Firdausi (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2023)
Song is an expressive text which is not an easy task to translate. Many considerations must be taken in order to create a well-produced song translation. In defining the song’s meaning, many procedures are needed to be done. Metaphor and untranslatability need to be presented as the analysis of the song translation. Metaphor which employs hidden and deepen meaning of a text comes along with the song’s expressive feature as a tool to deliver the writer’s feeling and emotions. Translation loss in metaphorical text is also presented while untranslatability deals with the linguistics, cultural, and compensation value of the text. The method used in this research was qualitative descriptive methodology. Metaphorical analysis was done to scrutinize the unseen feature of the text’s meaning. Translation loss in metaphorical view is also being presented in order to reveal the equivalence and inequivalence of the song translation. Two kinds translation loss are found, inevitable and avertable. Untranslatability dealt with the song’s linguistic and cultural phenomenon such as alliteration, assonance, and rhyme. Compensation which deals with untranslatability is also explained in this paper. Compensation in Kind, Compensation in Place, and Compensation in Merging are used to deal with the translation loss of the metaphorical sense of the song.